Telecommunications and data communications handbook - Horak, Ray (Wiley-Interscience, 2007)
For an accessible and comprehensive survey of telecommunications and data communications technologies and services, consult the Telecommunications and Data Communications Handbook, which includes information on origins, evolution and meaningful contemporary applications. Find discussions of technologies set in context, with details on fiber optics, cellular radio, digital carrier systems, TCP/IP, and the Internet. Explore topics like Voice over Internet Protocol (VoIP); 802.16 & WiMAX; Passive Optical Network (PON); 802.11g & Multiple Input Multiple Output (MIMO) in this easily accessible guide without the burden of technical jargon.